2017
DOI: 10.1016/j.aeolia.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Comments on ‘Influence of measurement uncertainties on fractional solubility of iron in mineral aerosols over the oceans’ Aeolian Research 22, 85–92

Abstract: ReuseUnless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Online record for this item. Where records identify the publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…Although in the literature there are recent estimates of trace metals solubility from dust (e.g., Chance et al, ; López‐García et al, ; Mackey et al, ; Ravelo‐Pérez et al, ; Winton et al, ), solubility percentages are usually as variable as reported values of atmospheric dust deposition in the ocean. The reasons for such variability include the origin, load, and geochemical characteristics of dust (Baker et al, ; Jickells et al, ; Sholkovitz et al, ) as well as a lack of consensus among the methodologies used for its estimation (Meskhidze et al, ; Raiswell et al, ; Schulz et al, ). Thus, to calculate the atmospheric supply of soluble metals from the total fluxes of Fe and Mn, we selected as the most representative for our study, Fe and Mn solubility percentages reported for soils from the nearest semiarid region and dust samples from the coastal portion of the CCS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in the literature there are recent estimates of trace metals solubility from dust (e.g., Chance et al, ; López‐García et al, ; Mackey et al, ; Ravelo‐Pérez et al, ; Winton et al, ), solubility percentages are usually as variable as reported values of atmospheric dust deposition in the ocean. The reasons for such variability include the origin, load, and geochemical characteristics of dust (Baker et al, ; Jickells et al, ; Sholkovitz et al, ) as well as a lack of consensus among the methodologies used for its estimation (Meskhidze et al, ; Raiswell et al, ; Schulz et al, ). Thus, to calculate the atmospheric supply of soluble metals from the total fluxes of Fe and Mn, we selected as the most representative for our study, Fe and Mn solubility percentages reported for soils from the nearest semiarid region and dust samples from the coastal portion of the CCS.…”
Section: Methodsmentioning
confidence: 99%
“…its estimation (Meskhidze et al, 2016;Raiswell et al, 2017;Schulz et al, 2012). Thus, to calculate the atmospheric supply of soluble metals from the total fluxes of Fe and Mn, we selected as the most representative for our study, Fe and Mn solubility percentages reported for soils from the nearest semiarid region and dust samples from the coastal portion of the CCS.…”
Section: Saw and Their Relative Contribution To The Annual And Seasonmentioning
confidence: 99%
“…The inorganic materials are minerals (or mineral aggregates) whose properties are modified by size and by the nature of the organic admixtures and/or complexes. There are a variety of techniques (Shi et al, 2012;Raiswell et al, 2017) available to study the CNFe fraction. These techniques include; scanning electron microscopy (SEM), high resolution transmission electron microscopy (HR-TEM), energy dispersive X-ray spectrometry (EDX) and selective area X-ray diffraction (SAED), all of which provide compositional, structural, and mineralogical information down to nanometre scales.…”
Section: Dissolved Ironmentioning
confidence: 99%
“…The particulate fraction is commonly defined in terms of fractional solubility which is the percentage of total Fe that passes through a 0.2, 0.4, or 0.45 µm filter after treatment with a specified extractant (Meskhidze et al, 2016;Raiswell et al, 2017). Unfortunately a wide variety of extraction techniques are commonly used such that fractional solubilities vary widely, e.g., the fractional solubility of aeolian dusts ranges from 0.001 to 80% (Jickells and Spokes, 2001;Baker and Croot, 2010).…”
Section: Particulate Fementioning
confidence: 99%
“…Additional paleodata from marine sediment cores, as well as future improvements in ocean biogeochemistry models, also driven by data from initiatives such as GEOTRACES [191] or process-based field campaigns, are needed to better quantify iron solubility [192][193][194] and indirect effects of dust on the ocean carbon cycle. Recent developments in explicitly representing mineralogy and aging in dust models [195][196][197] will provide enhanced tools to derive dust-borne iron inputs to the ocean, especially if also used for paleoclimate experiments and notably for the LGM [99].…”
Section: Indirect Impacts On Biogeochemical Cyclesmentioning
confidence: 99%